CEO Entrepreneurial Leadership and Performance Outcomes of Top Management Teams in Entrepreneurial Ventures: The Mediating Effects of Psychological Safety2. (25th September 2018) - Miao, Qing; Eva, Nathan; Newman, Alexander; Cooper, Brian
Abstract : This study examines whether the exhibition of entrepreneurial leadership by CEOs within entrepreneurial ventures fosters higher levels of top management team performance and job performance of team members, and whether psychological safety explains such effects. Utilizing four waves of multisource, multilevel data from 262 team members across 56 top management teams, we find that the exercise of entrepreneurial leadership by the CEO leads to higher levels of performance at the team and individual levels, and that psychological safety mediates such relationships.